Macro- and Microhabitat Predictors of Nest Success and Hatchling Survival in Eastern Box Turtles (Terrapene carolina carolina) and Spotted Turtles (Clemmys guttata) in Oak Savanna Landscapes - Refsnider, Jeanine M.; Carter, Sarah E.; Diaz, Alexis; Hulbert, Austin C.; Kramer, Gunnar R.; Madden, Paige; Streby, Henry M. (Frontiers in Ecology and Evolution, 2022)
Differing selection pressures on stationary nest contents compared to mobile offspring mean that the nest-site characteristics resulting in the highest nest success may not be the same characteristics that result in the highest survival of juveniles from those nests. In such cases, maternal nest-site choice may optimize productivity overall by selecting nest sites that balance opposing pressures on nest success and juvenile survival, rather than maximizing survival of either the egg or the juvenile stage. Determining which macro- and microhabitat characteristics best predict overall productivity is critical for ensuring that land management activities increase overall recruitment into a population of interest, rather than benefiting one life stage at the inadvertent expense of another. We characterized nest-site choice at the macro- and microhabitat scale, and then quantified nest success and juvenile survival to overwintering in two declining turtle species, Eastern box turtles and spotted turtles, that co-occur in oak savanna landscapes of northwestern Ohio and southern Michigan. Nest success in box turtles was higher in nests farther from macrohabitat edges, constructed later in the year, and at greater total depths. In contrast, survival of juvenile box turtles to overwintering was greater from nests under less shade cover and at shallower total depths. Spotted turtle nest success and juvenile survival were so high that we were unable to detect relationships between nest-site characteristics and the small amount of variation in survival. Our results demonstrate, at least for Eastern box turtles, a tradeoff in nest depth between favoring nest success vs. juvenile survival to overwintering. We suggest that heterogeneity in microhabitat structure within nesting areas is important for allowing female turtles to both exercise flexibility in nest-site choice to match nest-site characteristics to prevailing weather conditions, and to place nests in close proximity to habitat that will subsequently be used by hatchlings for overwintering.